(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Thirty nine species of insect pests were found to infest soybean crop at their different growth stages in Noakhali region of Bangladesh during January to May, 2010 and 2011. Among the recorded pest species, six species namely, hairy caterpillar, Spilarctia obliqua (Walker); leaf roller, Lamprosema indicata F; common cutworm, Spodoptera litura F; pod borer, Helicoverpa armigera (Hubner); stem fly, Ophiomyia phaseoli (Tryon) and white fly; Bemisia tabaci Genn. were considered as the major pests while the rests were of minor importance on the basis of population densities per plant, nature and extent of damages, and yield reductions. Most of the major and minor pests appeared in the crop during vegetative to flowering stages (30-50 Days after sowing) and the maximum insect population and their infestation occurred during flowering and pod formation stages of the crop throughout the study period. J. Asiat. Soc. Bangladesh, Sci. 39(1): 1-8, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16027